Methodology for the analysis and assessment of panoramic views of urbanised landscape - Dijokienė, Dalia; Alistratovaite-Kurtinaitiene, Inesa (Landscape Architecture and Art, 2024)
The article briefly discusses the methodological assumptions of panoramic view and silhouette analysis and assessment, which the authors have summarised by analysing the studies of other researchers and international guidance documents, and supplemented with their own insights. It is concluded that the assessment of a specific valuable view should include a discussion of the viewing conditions of the area in question from specific viewpoints and a definition of the sector of view and the barriers to view. The view should be analysed and then it must be specified what specifically is valuable in that view – the expression of elements visible in the view, domination and obscuring of objects, the existing relationship/proportion of natural and anthropogenic elements, also possibilities and peculiarities of visual links between objects/areas. The paper presents the authors’ proposed sequence of research steps and evaluation method, which includes: (1) selection of relevant viewpoints of the territory under study; (2) description and assessment of view sectors; (3) analysis of relevant panoramas; (4) identification of possible changes in the relationship between the natural environment and the built environment in the panoramic views, and presentation of recommendations. The methodology described in the paper is illustrated by the authors’ feasibility study for the development of the northern part of Žvėrynas (Vilnius district) in 2021. The research method presented in the paper allows to make reasoned decisions on the integration/non-integration of new development in the existing valuable urbanised landscape.